Modernization of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Program: Rationale and Overview of the THIS-WIC (Telehealth Intervention Strategies for WIC) Project - Catherine Wright; Pascasie Adedze; Alice Ammerman; Lauren Au; Alan Barnosky; Jonathan Blitstein; Karen Castellanos-Brown; Sheryl Cates; Madhur Chandra; Kenneth Kwan Ho Chui; Katharine Clarke; Christina Economos; et al. (Journal of Nutrition Education and Behavior, 2026)

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Environmental Gradients Decouple Demographic and Adaptive Connectivity in a Highly Mobile Coastal Marine Species - Chris J. Brauer; Andrea Bertram; Jonathan Sandoval‐Castillo; Anthony Fowler; Justin D. Bell; Paul Hamer; Maren Wellenreuther; Luciano B. Beheregaray (Molecular Ecology, 2026)
Understanding how eco‐evolutionary processes shape genetic variation and persistence in marine species with highly variable recruitment dynamics and dispersal potential remains a fundamental challenge, particularly when considering the interplay between gene flow and local adaptation. Here, we employed a seascape genomics approach to investigate population connectivity and local adaptation in Australasian snapper ( Chrysophrys auratus , Sparidae) along 1500 km of the environmentally heterogeneous southern Australian coastline. Using genome‐wide SNPs, we identified distinct eastern and western regional populations aligned with known biogeographical regions. Genotype‐environment association analyses revealed 855 candidate adaptive loci associated with environmental variation, including temperature, salinity and primary productivity. Connectivity analyses using neutral markers indicated high gene flow within both eastern and western regions, while candidate adaptive loci revealed substantially reduced connectivity, especially for Northern Spencer Gulf and West Coast populations. This contrast implies a decoupling of demographic and adaptive connectivity, in which strong environmental gradients appear to reduce the effective exchange of adaptive variation despite high overall connectivity. Our results support contingent migration as a potential mechanism modulating the balance between local adaptation and gene flow in this economically and ecologically important marine species. These findings might also have implications for regional management of other coastal fisheries that are experiencing substantial declines. As climate change alters coastal marine environments around the world, the dynamics of local recruitment, site fidelity and local adaptation are expected to change. This highlights the importance of integrating knowledge about eco‐evolutionary processes into marine resource management, fisheries stock assessment, and restocking and stock enhancement activities.

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Differential survival of Ilyanassa obsoleta to water temperature and association with the non-native red alga Gracilaria vermiculophylla - Timothy S. Lee; Amy E. Fowler; Jessica R. Largen; Jonathan P. Russo; Zackary J. Schlegel; Dawson K. Wright; April M. H. Blakeslee (Hydrobiologia, 2025)
Along the U.S. east coast, the widespread non-native red alga Gracilaria vermiculophylla provides habitat for an array of macroinvertebrates, including the eastern mudsnail Ilyanassa obsoleta . Though I. obsoleta tolerates a wide temperature range, increases in summer water temperatures may enhance mortality; furthermore, the presence of non-native algae in rising seawater temperatures could exacerbate harmful conditions. We tested how the presence or absence of G. vermiculophylla influenced snail mortality across a range of summer temperatures over a 3-week period. We found that I. obsoleta survived the longest in the lowest temperature (27 °C), followed by the medium (32 °C), and lastly the highest (36 °C) where all snails died within 2 days. Mortality was also higher and faster for snails in the presence versus absence of G. vermiculophylla . We suspected dissolved oxygen became very low at the higher temperatures with G. vermiculophylla ; thus we conducted a laboratory-based dissolved oxygen experiment. We found that G. vermiculophylla degraded and oxygen declined faster at the highest temperature treatment, thereby creating anoxic conditions. Altogether, our results demonstrate that G. vermiculophylla could enhance anoxic conditions at high summer temperatures, potentially leading to enhanced faunal mortality.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Boom‐bust dynamics in biological invasions: towards an improved application of the concept - David L. Strayer; Carla M. D'Antonio; Franz Essl; Mike S. Fowler; Juergen Geist; Sabine Hilt; Ivan Jarić; Klaus Jöhnk; Clive G. Jones; Xavier Lambin; Alexander W. Latzka; Jan Pergl; et al. (Ecology Letters, 2017)
Boom‐bust dynamics – the rise of a population to outbreak levels, followed by a dramatic decline – have been associated with biological invasions and offered as a reason not to manage troublesome invaders. However, boom‐bust dynamics rarely have been critically defined, analyzed, or interpreted. Here, we define boom‐bust dynamics and provide specific suggestions for improving the application of the boom‐bust concept. Boom‐bust dynamics can arise from many causes, some closely associated with invasions, but others occurring across a wide range of ecological settings, especially when environmental conditions are changing rapidly. As a result, it is difficult to infer cause or predict future trajectories merely by observing the dynamic. We use tests with simulated data to show that a common metric for detecting and describing boom‐bust dynamics, decline from an observed peak to a subsequent trough, tends to severely overestimate the frequency and severity of busts, and should be used cautiously if at all. We review and test other metrics that are better suited to describe boom‐bust dynamics. Understanding the frequency and importance of boom‐bust dynamics requires empirical studies of large, representative, long‐term data sets that use clear definitions of boom‐bust, appropriate analytical methods, and careful interpretations.

Effects of acute pramipexole on preference for gambling-like schedules of reinforcement in rats - Patrick S. Johnson; Gregory J. Madden; Adam T. Brewer; Jonathan W. Pinkston; Stephen C. Fowler (Psychopharmacology, 2011)

Timing and space usage are disrupted by amphetamine in rats maintained on DRL 24-s and DRL 72-s schedules of reinforcement - Stephen C. Fowler; Jonathan Pinkston; Elena Vorontsova (Psychopharmacology, 2009)

Clozapine and prazosin slow the rhythm of head movements during focused stereotypy induced by d-amphetamine in rats - Stephen C. Fowler; Jonathan W. Pinkston; Elena Vorontsova (Psychopharmacology, 2007)

Millennia‐long tree‐ring records from Tasmania and New Zealand: a basis for modelling climate variability and forcing, past, present and future - Edward R. Cook; Brendan M. Buckley; Jonathan G. Palmer; Pavla Fenwick; Michael J. Peterson; Gretel Boswijk; Anthony Fowler (Journal of Quaternary Science, 2006)
Progress in the development of millennia‐long tree‐ring chronologies from Australia and New Zealand is reviewed from the perspective of modelling long‐term climate variability there. Three tree species have proved successful in this regard: Huon pine ( Lagarostrobos franklinii ) from Tasmania, silver pine ( L. colensoi ) from the South Island of New Zealand, and kauri ( Agathis australis ) from the North Island of New Zealand. Each of these species is very long‐lived and produces abundant quantities of well‐preserved wood for extending their tree‐ring chronologies back several millennia into the past. The growth patterns on these chronologies strongly correlate with both local and regional warm‐season temperature changes over significant areas of the Southern Hemisphere (especially Huon and silver pine) and to ENSO variability emanating from the equatorial Pacific region (especially kauri). In addition, there is evidence for significant, band‐limited, multi‐decadal and centennial timescale variability in the warm‐season temperature reconstruction based on Huon pine tree rings that may be related to slowly varying changes in ocean circulation dynamics in the southern Indian Ocean. This suggests the possibility of long‐term climate predictability there. Copyright © 2006 John Wiley & Sons, Ltd.